Impact of Social Isolation Due to COVID-19 on Daily Life Activities and Independence of People over 65: a Cross-Sectional Study - Frutos, María Laura (2023)
The mandatory confinement caused by the COVID-19 pandemic has significantly affected the older adult population. The main objective of this study is to assess independence in basic activities of daily living (BADL) and instrumental activities of daily living (IADDL) of people over 65 years of age during social, preventive, and compulsory isolation due to COVID-19, identifying and quantifying the activities of personal independence that present difficulties in their execution. Design: A cross-sectional study. Settings: Private’s health insurance Hospital, Córdoba, Argentina. Participants: A total of 193 participants with mean age of 76.56 years (121 women and 72 men) who met inclusion criteria were included in the study. Interventions: A personal interview was conducted between July and December 2020. Sociodemographic data were collected, and perceived independence was assessed. Outcomes measures: The Barthel index and the Lawton and Brody scale were used to assess independence of basic and instrumental activities of daily living. Results: Minimal limitations were noted with function. The activities that represented the greatest difficulties were going up and down stairs (22%) and moving around (18%), and the greatest difficulties in instrumental activities of daily living were shopping (22%) and preparing food (15%). Conclusions: COVID-19 has caused isolation, leading to functional limitations for many, especially older adults. Perceived declines in function and mobility may lead to decreased independence and safety for the older adult; therefore, preventative planning and programming should be considered.